Система вищої освіти України в європейському освітньому просторі: місце та перспективи розвитку - Раєвнєва, Олена Валентинівна; Аксьонова, Ірина Вікторівна (Видавничий дім "Інжек", 2020)
Стаття присвячена визначенню міжнародної позиції системи вищої освіти (СВО) України в європейському освітньому середовищі. Доведено, що сучасний етап розвитку світової системи вищої освіти характеризується суттєвими трансформаціями, які змінюють парадигму функціонування традиційного університету на парадигму формування інноваційно-активного закладу вищої освіти (ЗВО) підприємницького типу. Метою статті є розробка методичного підходу до визначення привабливості національної системи вищої освіти в європейському освітньому просторі з урахуванням сучасних трендів трансформації університетів у підприємницькі суб’єкти господарювання. Запропоновано підхід, який на підставі проведення пошукових експериментів дозволяє здійснити кластеризацію України та 27 країн Європи і визначити не тільки загальний рівень привабливості за період 2013–2017 рр., але й (за рахунок проведення просторової кластеризації за 2013, 2015 і 2017 рр.) окремо виділити латентні тенденції (позитивні чи негативні) у рівнях привабливості аналізованих країн. Сформовано інформаційний простір групування країн, що за рахунок поєднання індикаторів (ментальна готовність суспільства до отримання вищої освіти; фінансова готовність/можливість уряду до підтримки розвитку системи вищої освіти; готовність університетів як структурних елементів системи вищої освіти до надання якісних освітньо-наукових послуг) дозволяє отримати системне уявлення про феномен привабливості системи вищої освіти. Проведені розрахунки показали, що національна СВО втрачає свої високі міжнародні позиції та потребує глибоких системних модернізацій у напрямку створення стимулюючого підґрунтя розвитку автономних, інноваційно-активних ЗВО підприємницького типу.

The article is concerned with defining the international position of the higher education system (HES) of Ukraine in the European educational environment. It is proved that the current stage of development of the world higher education system is characterized by significant transformations that change the paradigm of the functioning of the traditional university to the paradigm of the formation of an innovative-active higher education institution (HEI) of the entrepreneurial type. The article is aimed at developing a methodical approach to determining the attractiveness of the national system of higher education in the European educational space, taking into account modern trends of transformation of universities into entrepreneurial business entities. The approach, which on the basis of search experiments allows to cluster Ukraine and 27 European countries and determine not only the overall level of attractiveness for the period 2013–2017, but also (due to spatial clustering for 2013, 2015 and 2017) separately allocate the latent trends (both positive and negative) in the attractiveness levels of the analyzed countries, is proposed. The information space of grouping of countries is formed, which due to the combination of indicators (mental readiness of society to obtain higher education; financial readiness/government opportunity to support the development of the higher education system; readiness of universities as structural elements of the higher education system to provide high-quality educational and scientific services) allows to get a systematic idea of the phenomenon of attractiveness of the higher education system. The carried out computations showed that the national HES is losing its high international positions and requires deep systemic modernization in the direction of creating a stimulating basis for the development of autonomous, innovation-active HEIs of the entrepreneurial type.
The Higher Education System of Ukraine in the European Educational Space: Place and Development Prospects
Keywords: інноваційно-активний університет; система вищої освіти; кластерний аналіз; привабливість СВО; індикатори привабливості; innovation-active university; higher education system; cluster analysis; attractiveness of HES; attractiveness indicators